The Role of Intelligence in Countering the Threat of Used Imported Clothing Smuggling to Indonesia's Economic Security - Arnolda, Ralex; Widyarsih, A. Victoria Rahajeng; Sunny, Amril Gaffar (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
Public interest in used imported clothing is increasing due to various factors. The government has made various efforts to prevent the entry and circulation of used imported clothing through the creation of regulations, supervision and enforcement measures. However, the existence of used imported clothing remains latent in the community. This condition poses a threat to economic resilience, especially to the clothing industry, which is one of the mainstay industries of the Indonesian economy. This research will analyze the threat posed by the presence of used clothing through four stages of intelligence analysis. Then, it will categorize whether the threat of second-hand clothing is included in the threat capable of disrupting economic resilience. In addition, this research will use information obtained from interviews with informants to strengthen the results of the analysis. The data and information obtained will be triangulated to strengthen the results of the analysis. The results of this study found that the threat of used imported clothing is included in the moderate to serious threat level because it can result in shocks to industrial and economic output/production, increased unemployment, instability of exchange rates and foreign exchange reserves, and health threats. If left unchecked, this latent threat could pose social and economic risks if it reaches its culmination point. This research found that there is a need to strengthen and affirm the laws and regulations. In addition, this study found that at the operational and policy tactical level, the role of intelligence needs to be improved to prevent the presence of imported used clothing imports to a non-threatening point, such as by improving early detection measures, operational cooperation between institutions, exchanging human resource recruitment and intelligence capacity building.